2021
DOI: 10.1155/2021/1339683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combining Immersion Therapy with Shengji Ointment on Wound Healing Rate and Adverse Reaction Rate in Patients with Second-Degree Burn

Abstract: Objective. To explore the effect of combining immersion therapy with Shengji ointment on wound healing rate and adverse reaction rate (ARR) in patients with second-degree burn. Methods. The data of 80 patients with second-degree burn treated in our hospital from February 2019 to February 2020 were retrospectively analyzed by the means of retrospective study, and the patients were equally divided into the treatment group and the control group according to their admission order, with 40 cases each. Immersion the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A total of 1010 distinctive studies were found, of which 13 studies (between 2008 and 2022) satisfied the inclusion criteria and were comprised in the study. [25][26][27][28][29][30][31][32][33][34][35][36][37] This metaanalysis study based on 13 studies included 1073 subjects with pressure ulcer wound at the start of the study; 593 of them were using traditional Chinese medicine treatments, and 480 were control for pressure ulcer wounds. All studies evaluated the effect of Chinese herbal topical medicine, acupuncture, and moxibustion on pressure ulcer wound healing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1010 distinctive studies were found, of which 13 studies (between 2008 and 2022) satisfied the inclusion criteria and were comprised in the study. [25][26][27][28][29][30][31][32][33][34][35][36][37] This metaanalysis study based on 13 studies included 1073 subjects with pressure ulcer wound at the start of the study; 593 of them were using traditional Chinese medicine treatments, and 480 were control for pressure ulcer wounds. All studies evaluated the effect of Chinese herbal topical medicine, acupuncture, and moxibustion on pressure ulcer wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis study based on 13 studies included 1073 subjects with pressure ulcer wound at the start of the study; 593 of them were using traditional Chinese medicine treatments, and 480 were control for pressure ulcer wounds. [25][26][27][28][29][30][31][32][33][34][35][36][37] Traditional Chinese medicine treatments had significantly higher complete healing, and curative ratio post-treatment compared with control for subjects with pressure ulcer wounds. However, the analysis of outcomes should be performed with consideration because of the low number of selected studies and the low sample size of most of the selected studies found for the meta-analysis, 10 out of 13 studies with ≤100 subjects as sample size; recommending the need for other studies to confirm these findings or perhaps to significantly impact confidence in the influence evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial phenotype analysis revealed that many anaerobes were significantly decreased due to burn injury but showed recovery in the late time after burn, potentially providing insight into the microbial succession associated with burn injury (Lovell et al, 2022). Burn injury can be divided into four types: first-degree burn, superficial second-degree burn, deep partial-thickness burn, and thirddegree burn (Guo and Yu, 2021). Deep partial-thickness burn wounds are characterized by blisters that extend into the reticular dermal layer and have a higher risk of chronic inflammation of the dermis (Lukiswanto et al, 2019), which can lead to infection or scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Burn injury can be divided into four types: first-degree burn, superficial second-degree burn, deep partial-thickness burn, and third-degree burn ( Guo and Yu, 2021 ). Deep partial-thickness burn wounds are characterized by blisters that extend into the reticular dermal layer and have a higher risk of chronic inflammation of the dermis ( Lukiswanto et al, 2019 ), which can lead to infection or scarring.…”
Section: Discussionmentioning
confidence: 99%